2017
DOI: 10.1080/01440365.2017.1289673
|View full text |Cite
|
Sign up to set email alerts
|

Defending the Accused: The Impact of Legal Representation on Criminal Trial Outcomes in Victoria, Australia 1861–1961

Abstract: Access to legal representation by accused felons was entrenched as part of the adversarial system from the early nineteenth century, but a substantial minority of defendants remained undefended at superior court level well into the twentieth century. Using a sample of criminal trials collected across a crucial hundred-year period that saw the development of incipient legal assistance schemes, this article seeks to examine what effect the presence of defence counsel had on individual trial results. It is shown … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…The analysis of rural versus urban crime in Australia has relied on state capitals to stand for "urban" settlements (Nagy 2021;Nagy and Piper 2019;Piper and Finnane 2017a). Ironically, this approach highlights urbanity, since it describes the balance of the state (in NSW, over 300,000 square miles) as "rural" territory.…”
Section: Methods Of Defining Ruralitymentioning
confidence: 99%
See 2 more Smart Citations
“…The analysis of rural versus urban crime in Australia has relied on state capitals to stand for "urban" settlements (Nagy 2021;Nagy and Piper 2019;Piper and Finnane 2017a). Ironically, this approach highlights urbanity, since it describes the balance of the state (in NSW, over 300,000 square miles) as "rural" territory.…”
Section: Methods Of Defining Ruralitymentioning
confidence: 99%
“…Caroline Buckman and her children, unsupported by their father, were so poor that they had survived for months on flour and rabbits; consequently, she could ill afford to hire a solicitor or a barrister to represent her. Australian historical criminological studies have confirmed the deleterious impact of poverty on the quality of legal defenses (Piper and Finnane 2017a;2017b). However, one of the state's top lawyers from an illustrious legal family, Richard Windeyer, volunteered to represent the accused pro bono, and he ensured that the woman was released on bail (possibly guaranteed with his own funds).…”
Section: One Of Us Had To Diementioning
confidence: 99%
See 1 more Smart Citation
“…Criminological concerns with understanding changing patterns of crime, policing and punishment are joined with legal historical questions about the changing process of prosecution. Accessing original data enables researchers to explore questions rarely contemplated in historical studies of the criminal justice system, such as the specific roles and impact of defence lawyers (Piper and Finnane, 2017a, 2017b) or the victim characteristics associated with the prosecution of offences against person or property (Finnane and Kaladelfos, 2016; Piper, 2018). In contrast to the focus of official record-keeping on the criminal offender, the data accessed by the Prosecution Project enable us to contemplate a history in which all parties to the process of the trial recover their historical place.…”
Section: Project Aimsmentioning
confidence: 99%